2010
DOI: 10.1111/j.1468-0084.2010.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Why has China Grown So Fast? The Role of Physical and Human Capital Formation*

Abstract: Cross-province growth regressions for China are estimated for the reform period. Two research questions are asked. Can the regressions help us to understand why China as a whole has grown so fast? What types of investment matter for China's growth? We address the problem of model uncertainty by adopting two approaches to model selection to consider a wide range of candidate predictors of growth. Starting from the baseline equation, the growth impact of physical and human capital is examined using panel data te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 87 publications
(122 reference statements)
5
47
1
Order By: Relevance
“…Easterly and Levine (2001) argue that the major empirical regularities of economic growth indicate an important role for the residual rather than for factor accumulation. Productivity growth is also regarded as an important underlying reason for China's remarkable economic growth since 1978, in addition to other proximate determinates such as physical and human capital accumulation (see, for instance, Ding and Knight 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Easterly and Levine (2001) argue that the major empirical regularities of economic growth indicate an important role for the residual rather than for factor accumulation. Productivity growth is also regarded as an important underlying reason for China's remarkable economic growth since 1978, in addition to other proximate determinates such as physical and human capital accumulation (see, for instance, Ding and Knight 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dollar and Wei (2007) found that the state-owned firms still have significantly lower returns to capital, on average, than domestic private or foreign-owned firms, and calculate that the misallocation of resources is worth some 5 per cent of GDP. Ding and Knight (2008) examined the impact of fixed-asset investment on GDP growth per capita over the period 1980-2000 and found that investment by SOEs was wasteful: increasing the share of SOEs in total fixed investment by one percentage point was associated with a decline in the growth rate of 0.08 percentage points. Chen et al (2011) also show that public intervention in SOEs through majority state ownership and/or the appointment of connected managers has distorted these firms' investment behaviour and harmed their investment efficiency.…”
Section: Surplus Monetary Liquidity Soe Investments and Financial Frmentioning
confidence: 99%
“…In addition, researchers have accepted the idea that fixed asset investment and FDI are major driving forces of China's economy and that the impact of human capital on urban growth is less significant (Arayama & Miyoshi, 2004;Chen & Fleisher, 1996;Wei, Liu, Song, & Romilly, 2010). Several studies have shown a positive and significant relationship between human capital and economic growth (Ding & Knight, 2011;Mestieri, Schauer, & Townsend, 2017;Song, Chu, & Chao, 2000). Glaeser and Lu (2018) found that one year more city-level education increases individual hourly wage by 22.0%.…”
Section: Zheng Et Almentioning
confidence: 99%